Palynostratigraphy, Paleoenvironments and Kerogen Evaluation of the Campanian-Maastrichtian Enugu Shale, Anambra Basin, Nigeria - M. A. Olayiwola; E. U. Durugbo; O. T. Fajemila (Fountain Journal of Natural and Applied Sciences (FUJNAS), 2020)
Palynological and palynofacies analyses were used to investigate the paleoenvironments and hydrocarbon potential of the Campanian-Maastrichtian Enugu Shale, Anambra Basin, Nigeria. The palynological analysis of twenty-three outcrop samples revealed diverse and abundant palynomorph assemblages, which consisted of pteridophyte spores 46.82%, angiosperms 36.9%, gymnosperms 1.48 %, algae 5.65%, dinoflagellate cysts 5.1%, fungal elements 1.17%, acritarchs 0.34%, microforaminiferal wall linings 0.01% and miscellaneous palynomorphs (Charred graminae cuticle, incertae sedis) 2.53%. Seven informal palynological assemblage zones (PAZ) with corresponding eustatic sea level changes were delineated. Palynofacies analysis revealed four palynofacies types I to IV based on the percentage relative abundances of the sedimentary organic matter (SOM). Palynofacies types P-I and P-II suggest proximal fluvio-deltaic setting, while P-III and P-IV reflect a heterolithic-oxic shelf (proximal shelf) environment, indicative of deposition in an oxidizing condition. Results of the Spore Colour Index (SCI) and Thermal Alteration Index (TAI) analyses indicate that the Enugu shales are thermally immature.